Risk Factors for Major Bleeding during Prolonged Anticoagulation Therapy in Patients with Venous Thromboembolism: From the COMMAND VTE Registry - Kim, Kitae; Yamashita, Yugo; Morimoto, Takeshi; Kitai, Takeshi; Yamane, Takafumi; Ehara, Natsuhiko; Kinoshita, Makoto; Kaji, Shuichiro; Amano, Hidewo; Takase, Toru; Hiramori, Seiichi; Oi, Maki; Akao, Masaharu; Kobayashi, Yohei; Toyofuku, Mamoru; Izumi, Toshiaki; Tada, Tomohisa; Chen, Po-Min; Murata, Koichiro; Tsuyuki, Yoshiaki; Saga, Syunsuke; Sasa, Tomoki; Sakamoto, Jiro; Kinoshita, Minako; Togi, Kiyonori; Mabuchi, Hiroshi; Takabayashi, Kensuke; Shiomi, Hiroki; Kato, Takao; Makiyama, Takeru; Ono, Koh; Furukawa, Yutaka; Kimura, Takeshi; On behalf of the COMMAND VTE Registry Investigators (Thrombosis and Haemostasis, 2019)
Background There are limited data assessing the risk for bleeding on anticoagulation therapy beyond the acute phase in patients with venous thromboembolism (VTE). The present study aimed to identify risk factors for major bleeding during prolonged anticoagulation therapy in VTE patients.Patients and Methods The COMMAND VTE Registry is a multicenter registry enrolling 3,027 consecutive patients with acute symptomatic VTE. The current study population consisted of 2,728 patients who received anticoagulation therapy beyond the acute phase, after excluding those patients with major bleeding events (n = 48), death (n = 66), or loss to follow-up (n = 32) during the initial parenteral anticoagulation period within 10 days after diagnosis, and those without anticoagulation therapy beyond 10 days after diagnosis (n = 153).Results During the median follow-up period of 555 days, major bleeding occurred in 189 patients (70 patients within 3 months; 119 patients beyond 3 months) with fatal bleeding in 24 patients (13%). The cumulative incidence of major bleeding was 2.7% at 3 months, 5.2% at 1 year, and 11.8% at 5 years. Active cancer (hazard ratio [HR], 3.06, 95% confidence interval [CI], 2.23–4.18), previous major bleeding (HR, 2.38, 95% CI, 1.51–3.59), anemia (HR, 1.75, 95% CI, 1.27–2.43), thrombocytopenia (HR, 2.11, 95% CI, 1.27–3.33), and age ≥75 years (HR, 1.64, 95% CI, 1.22–2.20) were independently associated with an increased risk for major bleeding by the multivariable Cox regression model.Conclusion Major bleeding events were not uncommon during prolonged anticoagulation therapy in real-world VTE patients. Active cancer, previous major bleeding, anemia, thrombocytopenia, and old age were the independent risk factors for major bleeding.
Keywords: venous thromboembolism; bleeding; anticoagulation therapy; risk factor